The effectiveness of soaking Moringa leaves (Moringa oleifera L) on the internal quality of chicken eggs Gallus gallus domestica - Sukarman Hadi Jaya Putra; Sri Sulystyaningsih Natalia Daeng Tiring (Jurnal Biologi Tropis, 2021)
The purpose of this study was to analyze the effectiveness of soaking eggs using a solution of Moringa leaves for 24 hours on the internal quality of broiler eggs. Soaking aims to provide a layer on the pores of the egg shell so that it can keep the eggs from microbes and inhibit the release of gas from the egg. This type of research is experimental with Completely Randomized Design (CRD). The number of eggs used is 1000 eggs. The egg samples used are 420 eggs. The eggs used are in good condition, namely brown eggs, clean, intact, not cracked, texture smooth and oval in shape. The randomization method used random sampling in the form of a lottery system. Each of the 420 eggs is labeled. The eggs that were taken at random were divided into 4 treatment groups. Each treatment group consisted of 5 replications. Therefore, 20 treatment replications were obtained. Measurement of storage time and internal quality of eggs will be tested for 21 days. This is done to determine the level of egg resistance accurately, because the embryonic development period of the egg occurs for 21 days. Egg parameter measurements were carried out every day, at 08.00 WITA. Egg quality parameters were taken every 7 days. Egg quality parameters analyzed were egg white index, egg yolk index, and egg weight loss. All measurement data were analyzed by analysis of variance (ANOVA). If the results of the analysis have an effect, the Tukey test is continued with 95% confidence (ÃÂ±> 0.05). The data that has been analyzed explains that chicken eggs that get soaked in a solution of Moringa leaves have a higher index of egg yolk and egg white than eggs that are not soaked in a solution of Moringa leaves. The most optimal concentrations in maintaining the egg yolk and egg white index are 30% and 45% Therefore, soaking eggs with Moringa leaves serves to maintain the internal quality of eggs seen from the yolk index and egg white index.